Análisis de los incentivos tributarios e incidencia en el desarrollo económico del sector agrícola de la provincia de El Oro. - Blacio Gualpa, Viviana Veronica (My University, 2018)
Tax incentives are benefits that the State offers through a tax reform or tax policies to which taxpayers or taxpayers in the country are subject. These tax incentives are used by taxpayers to minimize their costs in the tax base to calculate their tax payable; However, there are taxpayers seeking to reduce the payment of their taxes through activities that use the option of evading taxes to pay less tax. For this reason, the tax administration has implemented controls, one of which is tax citizen training for the taxpayer to understand and practice the culture, ethics, morals and tax awareness and make the timely payment of their tax obligations in the time stipulated by the administration. tributary and be able to increase the economic development of the country distributed in the different provinces, areas that form a nation to reactivate the investment, creation of companies and generate sources of work. The general objective of this paper is to analyze the tax incentives that have influenced the economic growth of the province of El Oro. For the development of the work, the descriptive method of cross-sectional type to bibliographical sources was used to obtain information of great importance. In this way, tax incentives become a strategy for the government and benefit for taxpayers to reactivate the development and economic stability of the agricultural sector, in fact the agricultural sector is one of the sources of income for the province.
Los incentivos tributarios son beneficios que el Estado ofrece mediante una reforma tributaria o políticas fiscales a las que están sujetas los contribuyentes o sujetos pasivos en el país. Estos incentivos tributarios son utilizados por los contribuyentes para minimizar sus costos en la base imponible para calcular su impuesto a pagar; sin embargo existen sujetos pasivos que buscan disminuir el pago de sus tributos a través de actividades que utilizan la opción de evadir impuestos para cancelar menor tributo. Por ello la administración tributaria ha implementado controles uno de ellos es la capacitación ciudadana tributaria para que el sujeto pasivo comprenda y practique la cultura, ética, moral y conciencia tributaria y realice el pago oportuno de sus obligaciones fiscales en el tiempo estipulado por la a administración tributaria y poder incrementar el desarrollo económico del país distribuido en las diferentes provincias, áreas que forman a una nación para reactivar la inversión, creación de empresas y generar fuentes de trabajo. El objetivo general del presente trabajo es analizar los incentivos tributarios que han influido en el crecimiento económico de la provincia de El Oro. Para el desarrollo del trabajo se empleó el método descriptivo del tipo transversal a fuentes bibliográficas que permiten obtener información de suma importancia. De esta manera los incentivos tributarios se convierten en una estrategia para el gobierno y beneficio para los contribuyentes para reactivar el desarrollo y estabilidad económica del sector agrícola, en efecto el sector agrícola es una de las fuentes de ingresos para la provincia.
Keywords: INCENTIVOS TRIBUTARIOS; ADMINISTRACIÓN TRIBUTARIA; SECTOR AGRÍCOLA; CULTURA TRIBUTARIA